The final Neolithic and Chalcolithic settlement of Travessa das Dores (Ajuda – Lisboa) - Neto, Nuno (2020)
This paper presents the results of the archaeological excavations carried out at Travessa das Dores, Lisbon, before the construction of a new building at the location. The excavations were limited to the area affected by the new building. A significant number of pits was dug during the Final Neolithic into a Cretaceous marly limestone platform. Soon after, an important defensive ditched enclosure was installed in the same location. This is the first ditched enclosure excavated in Lisbon and north of the Tagus River. The artefact assemblages recovered from this two construction phases indicate a domestic occupation, with especially abundant fragments with indented edges indicating a single cultural phase, the Final Neolithic. During the Chalcolithic period, the site housed other, less important domestic settlements; several hearths were identified among the ditch fil, associated with Early and Full/Final Chalcolithic ceramics. Based on the results presented in this paper, the Travessa das Dores settlement may be considered the most important prehistoric site identified and excavated in the city of Lisbon.